Prediction of explosive decompression damage in elastomer seals - Routh, James Mathew (Cranfield University, 1999)
Elastomer seals are widely used in industry for containing gases and liquids. Seal failure can have significant environmental and financial implications far beyond the cost of the seal itself. Explosive decompression failure can cause catastrophic cracking of an elastomer seal, causing leakage. The objective of this research was to develop a modelling methodology to predict the onset of crack damage in elastomer seals under various operational conditions. The modelling methodology uses the finite element method to determine the performance of various elastomers under decompression conditions. The model takes into account seal and groove geometry, the non-linear behaviour of the material and the operational conditions seen by the seal. The model predicts crack initiations, locations and the orientation of the propagation. The model can also calculate the safe decompression time - required for no damage in the elastomer seal by using the methodology in reverse. To carry out the modelling methodology, certain input data are required. The data was determined by designing and constructing specialist test rigs. A permeation testing facility was developed to determine the diffusion, solubility and permeation characteristics of elastomers subject to gas pressure. The physical behaviour of the elastomers was determined through extensive uniaxial and equibiaxial tensile testing. The nature of the failure initiation points is determined by microscopic analysis of seal sections. Decompression tests were performed to validate the output of the model. Comparison of the model outputs with the decompression tests show a good correlation between the prediction and the occurrences, orientations and positions of cracks. The ability to predict damage in a quantitative manner was previously not available. The methodology will be developed into a knowledge-based software tool for use in industry to predict damage and develop new materials to resist explosive decompression.